ANALISIS RADIOAKTIVITAS ALAM PADA SAMPEL COKLAT DAN SUSU BUBUK MENGGUNAKAN SPEKTROMETER GAMMA - Sri Murniasih, ; Sukirno, ; Agus Taftazani, (Matematika dan Sains, 2010)
Radioactivity content analyzed on milk and chocolate powdered samples produced at the West Java, Central Java, and East Java, had been done by gamma spectrometry with Germanium Lithium (GeLi) detector equipped by MESTROTM software and Multi Channel Analyzer (MCA) to analysis radionuclide and gamma gross. While analysis beta gross was done using Low Background Counter (LBC) with Geiger Muller (GM) detector and Analog Digital Converter (ADC). Activity of K40 on all samples ranges from 577.50 ± 13.49 Bq/Kg to 150.98 ± 9.00 Bq/K; Th232 ranges from 21.29 ± 0.82 Bq/Kg to 4.72 ± 0.71 Bq/Kg; Pb212 ranges from 3.41 ± 0.20 Bq/Kg to 2.50 ± 0.11 Bq/Kg; Pb214 ranges from 7.39 ± 0.34 Bq/Kg to 0,65 ± 0,07 Bq/Kg; Ra226 ranges from 9,14 ± 0,97 Bq/Kg to 6,02 ± 0,61 Bq/Kg dan Bi214 ranges from 5.25 ± 2.26 Bq/Kg to 1.73 ± 0.52 Bq/Kg. While beta gross and gamma gross activities ranges from 513.8 ± 30.83 Bq/Kg to 277.3 ± 21.33 Bq/Kg and 861.94 ± 5.76 mBq/Kg to 5.10 ± 2.04 mBq/Kg. Radionuclide activity content in all of milk and chocolate powdered samples that safe to be consumed. Using statistic test of ANOVA (a0.05) method found that difference of sample has influence significant on the activity of K40 Tl208, Pb212, Pb214, Bi214, Ra226 and gamma gross radioactivity while on beta gross there is no significant influence on sample difference.TM software and Multi Channel Analyzer (MCA) to analysis radionuclide and gamma gross. While analysis beta gross was done using Low Background Counter (LBC) with Geiger Muller (GM) detector and Analog Digital Converter (ADC). Activity of K40 on all samples ranges from 577.50 ± 13.49 Bq/Kg to 150.98 ± 9.00 Bq/K; Th232 ranges from 21.29 ± 0.82 Bq/Kg to 4.72 ± 0.71 Bq/Kg; Pb212 ranges from 3.41 ± 0.20 Bq/Kg to 2.50 ± 0.11 Bq/Kg; Pb214 ranges from 7.39 ± 0.34 Bq/Kg to 0,65 ± 0,07 Bq/Kg; Ra226 ranges from 9,14 ± 0,97 Bq/Kg to 6,02 ± 0,61 Bq/Kg dan Bi214 ranges from 5.25 ± 2.26 Bq/Kg to 1.73 ± 0.52 Bq/Kg. While beta gross and gamma gross activities ranges from 513.8 ± 30.83 Bq/Kg to 277.3 ± 21.33 Bq/Kg and 861.94 ± 5.76 mBq/Kg to 5.10 ± 2.04 mBq/Kg. Radionuclide activity content in all of milk and chocolate powdered samples that safe to be consumed. Using statistic test of ANOVA (a0.05) method found that difference of sample has influence significant on the activity of K40 Tl208, Pb212, Pb214, Bi214, Ra226 and gamma gross radioactivity while on beta gross there is no significant influence on sample difference.